Detail in contemporary landscape architecture - McLeod, Virginia (London : Laurence King Publishers, 2012)
Featuring many of the world's most highly acclaimed landscape architects, this book presents 40 of the most recently completed and influential landscape designs. Each project is presented with color photographs, site plans and sections as well as numerous consistently styled construction details. Intended for architects, engineers and landscape architects, the book will also be invaluable for architecture, garden and landscape design students, for whom it will be a resource not only for understanding the work of the best contemporary landscape architects, but also as a tool for their own design work.
Keywords: Architecture--Details; Landscape architecture